Informed choice and its associated factors among women received immediate postpartum long-acting reversible contraceptives at public hospitals in Sidama Regional State, Ethiopia, 2022 - Beniyam Samuel; Berhan Tsegaye; Dubale Dulla; Amdehiwot Aynalem; Eskinder Israel; Meless Gebrie (BMC, 2023)
Abstract Introduction It is crucial to ensure the quality of family planning (FP) services through women's informed choice during the provision of long-acting reversible contraceptives. In Ethiopia, previous studies have focused on the quality of family planning services. However, much emphasis was not given to the informed choice of immediate postpartum long-acting reversible contraceptives (LARCs), particularly in the study area. This study determines the mangnitude of informed choice and associated factors among immediate postpartum women who received long-acting reversible contraceptives. Method An institution-based cross-sectional study was conducted from July 1 - August 31, 2022, among 373 immediate postpartum women who received long-acting reversible contraceptives at public hospitals in the Sidama regional state, Ethiopia. Women were selected and interviewed using a systematic random sampling technique and via a structured interviewer-administered questionnaire respectively. Data was collected using Kobo Toolbox software and then exported to the Statistical Package for Social science (SPSS) version 25 for analysis. A logistic regression model was used to identify the predictor variables. Results The magnitude of informed choice of long-acting reversible contraceptives was 23.5% (95% CI (19.6%-27.7%)). The messages through posters about long-acting reversible contraceptives at the facility (AOR 3.6, 95% CI (1.92-6.79), postpartum family planning counseling during antenatal care (AOR 2.8, 95% CI (1.2-6.4), previous contraceptive use (AOR 3.23, 95% CI (1.12-9.33), and being secondary and higher educated (AOR 2.92, 95%CI (1.27-6.73) and (AOR 5.7, 95% CI (2.267-14.669) respectively were factors significantly associated with informed choice during immediate postpartum family planning service. Conclusion and recommendation In the current study, nearly one-fourth of women were informed about LARCs. Socio-demographic factors, prior use of contraception, exposure to posters that have messages about long-acting reversible contraceptives, and postpartum family planning counselling during antenatal care are factors that affect the woman's ability to make an informed choice. There should be immediate PPFP counselling that focuses on a full range of contraceptive method choices to facilitate postpartum women's ability to make informed choices.